Comunidade de artrópodes ectoparasitos de duas espécies de Turdus linnaeus, 1758 (Passeriformes: turdidae) no sul do estado do Rio Grande do Sul, Brasil - Amaral, Hugo Leonardo da Cunha (2011)
This study aimed to describe the ectoparasitic arthropod community associated with syntopic populations of Turdus amaurochalinus and T. rufiventris in three areas of the Atlantic forest in the southern state of Rio Grande do Sul (RS), Brazil from July 2009 to June 2010. This study was a qualitative survey of feather mites (Acari: Astigmata), and both qualitative and quantitative surveys of chewing lice (Phthiraptera: Amblycera and Ischnocera), ticks (Acari: Ixodidae) and flies (Diptera: Hippoboscidae) for each host species. We analyzed the influence of host body weight and body length of captured birds on the abundance and species richness of ectoparasites in relation to the seasons. Altogether, we captured 36 specimens of T. amaurochalinus and 53 specimens of T. rufiventris. We identified two families of chewing lice, Menoponidae and Philopteridae, with Myrsidea sp. the most prevalent and abundant on both host species. For chewing lice, females were more predominant than males, except Menacanthus eurysternus on T. amaurochalinus. Chewing lice adults were more abundant than nymphs. The feather mite species most prevalent on T. amaurochalinus was Proctophyllodes weigoldi, and for T. rufiventris it was Trouessartia serrana. Analges sp. and Pteronyssoides sp. were not observed on T. rufiventris. We identified three species of ticks; Ixodes auritulus was the most prevalent and abundant on the birds. Ornithoica vicina was the only species of Diptera found and this was observed only on T. amaurochalinus. The greatest richness of ectoparasites occurred on T. amaurochalinus where we observed less mean richness in winter compared to spring and autumn; however, we observed no variation in the mean richness of ectoparasites for T. rufiventris during the same seasons.